Energy consumption of high-performance buildings: Design vs. Reality. (November 2019) - Cozza, Stefano; Chambers, Jonathan; Gambato, Carlo; Branca, Giovanni; Geissler, Achim; Patel, Martin K
Abstract: Studying the performance of highly efficient buildings is crucial for future policy, for example to inform decision making about whether to pursue further thermal improvement of buildings (insulation) or to rather foster investments in renewable resources. For this purpose, reliable values of the energy demand of new and retrofitted buildings are needed. However, there is evidence of a significant Energy Performance Gap (EPG) in buildings, defined as the difference between measured and calculated energy consumption. The objective of this paper is therefore to quantify the EPG in high efficiency buildings in Switzerland. The EPG was studied for 56 residential buildings, including various construction standards (Minergie, Minergie-P, and Minergie-A) and building types (new and retrofitted). The Minergie indexes were used as theoretical consumption, thereby representing the total final energy consumption for all needs of the buildings. These values were compared to data based on measurements. For the buildings in the sample the analysis yields a negative EPG of -14% (i.e. the median building consumes slightly less than its standard), indicating that the most efficient buildings are more robust to the EPG. However, this finding could be partly a consequence of the small sample used and its characteristics.